Analysis of interjections in Supporting Characters in the Novel “Rindu” by Tere Liye - Tri Andayani (Journal of Linguistica, 2024)
The use of Interjection in supporting supporting characters in the novel "Rindu" by Tere LiyeThe method used is qualitative descriptive. The subject is the author, and the object is the Suppport character’s.The primary data source for this study is the novel "Rindu" by Tere Liye. The data is that all interjections used by the support characters in the text will be identified and analyzed.A purposive sampling technique..Instruments Used in Research: Author, Novel "RIndu" by Tere Liye, and Notebook, table (datasheet). Data collection tools are first, textual content: Tere Liye's novel. The data collection process involves several steps:  Identification: Reading the novel to identify all instances of interjections used by the supporting character,  Cataloging and  classification Data Analysis Procedures are: 1. Identification of Interjections, 2.Classification of Interjections, 3. Contextual Analysis, 4.Frequency Analysis, and 5. Function Based on the results of the research, the most interjection words are the type of greeting and Farewell. Based on the results  the type of use of greetings and farewells interjection is the most in total, as many as 30 interjections by supporting character's : Daeng andipati wife, Anna, Elsa, etc. Meanwhile, the figure who uses greetings and farewells the most is Anna with 15 word. The novel "Rindu" by Tere Liye employs interjections effectively to build the characters and enhance the emotional depth of the story. Here are several ways interjections contribute to character development in the novel: Expressing Emotions, Revealing Personality, Creating Realistic Dialogue, Indicating Cultural Background, Enhancing Tension and Drama, and Character Relationships.